2011
DOI: 10.1007/s00464-010-1481-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic versus conventional laparoscopic right hemicolectomy: a comparison of short-term surgical results

Abstract: Our preliminary experience with SILS right hemicolectomy demonstrated the safety of the procedure and its feasibility in malignant colon cancer. Although SILS right hemicolectomy may provide a subjective cosmetic advantage, there was no benefit in the short-term surgical outcomes. SILS is very situational, requires more effort from the surgeon, and may not offer more patient comfort. More experience with SILS and prospective trials are needed to validate it as a more favorable alternative to conventional lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
118
6
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 11 publications
6
118
6
3
Order By: Relevance
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 47%
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 47%
“…Some reports have successfully mentioned its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain, and shorter recovery time. [13][14][15][16][17] To our knowledge, this is the first reported case of SILSþ1 TPE for advanced rectal cancer.…”
Section: Discussionmentioning
confidence: 74%
“…Another expected advantage of a small incision is the reduction of postoperative pain. None of the published reports assessed the postoperative pain or analgesic requirements (32)(33)(34)(35). Technical difficulties of single-access as the lack of triangulation and exposure, the inaxis view and conflicts between instruments are the most important challenges.…”
Section: Discussionmentioning
confidence: 99%